A chiral halogen bonding [3]rotaxane for recognition and sensing of biologically-relevant dicarboxylate anions - Lim, J; Marques, I; Félix, V; Beer, P (Wiley, 2017)
The unprecedented application of a chiral halogen bonding [3]rotaxane host system for discrimination of stereo- and E/Z geometric dicarboxylate anion guest isomers is described. Synthesised by a chloride anion templation strategy, the [3]rotaxane host recognises dicarboxylates via formation of 1:1 stoichiometric sandwich complexes, which is supported by molecular dynamics simulations that reveal the critical synergy of halogen and hydrogen bonding interactions in anion discrimination. In addition, the centrally located chiral (S)-BINOL motif of the [3]rotaxane's axle component facilitates the complexed dicarboxylate species to be sensed via a fluorescence response.